(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2020)
The purpose of this study is to analyze the evolution of the exports of the tuna sector to the European Union and its impact on the trade balance within a time frame between 2014 - 2018. Its investigative approach to obtaining the data it is qualitative-quantitative. It is structured based on a theoretical-conceptual and legal framework. The deductive, inductive methodologies allowed to expand the knowledge and its impact regarding the trade agreement with the European Union to measure its export strength of loin and canned Ecuadorian tuna. An analysis of prospective reflection is also proposed, considering possible scenarios, alternative solutions and improvements under traceability and differentiation criteria for the future of the sector. Among the main results obtained, it is determined that the tuna sector is vital for the economy, contributing 5% to GDP. In terms of trade balance, there is no evidence of a significant rebound in the increase in exports from the beginning of the trade agreement. Although there is evidence of a decrease at the level of imports of the oil segment, especially in 2014, which causes a noticeable effect on the Trade Balance. On the other hand, non-oil exports have been recovering until achieving an upward trend. This shows that non-oil exports, including tuna, are a key factor towards economic sustainability, which, while still highly dependent on oil revenues, has been weakening more strongly in the last five years.